2010
DOI: 10.1242/dmm.004648
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotection resulting from insufficiency of RANBP2 is associated with the modulation of protein and lipid homeostasis of functionally diverse but linked pathways in response to oxidative stress

Abstract: SUMMARYOxidative stress is a deleterious stressor associated with a plethora of disease and aging manifestations, including neurodegenerative disorders, yet very few factors and mechanisms promoting the neuroprotection of photoreceptor and other neurons against oxidative stress are known. Insufficiency of RAN-binding protein-2 (RANBP2), a large, mosaic protein with pleiotropic functions, suppresses apoptosis of photoreceptor neurons upon aging and light-elicited oxidative stress, and promotes age-dependent tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 23 publications
(68 citation statements)
references
References 77 publications
4
64
0
Order By: Relevance
“…Hence, we took an unbiased proteomic approach to screen and identify proteins with proteostatic changes between wild-type and Tg-Ranbp2 R2944A-HA ::Ranbp2 Ϫ/Ϫ mice. This survey also included another transgenic line with a mutation in the cyclophilin-like domain (CLD) of Ranbp2 (58) Ϫ/Ϫ were highly selective, because no changes were observed in the levels of other partners of Ranbp2, such as SUMO-1-RanGAP, Nr2e3, and COUP-TFI (data not shown) (89).…”
Section: R2944a-hamentioning
confidence: 99%
“…Hence, we took an unbiased proteomic approach to screen and identify proteins with proteostatic changes between wild-type and Tg-Ranbp2 R2944A-HA ::Ranbp2 Ϫ/Ϫ mice. This survey also included another transgenic line with a mutation in the cyclophilin-like domain (CLD) of Ranbp2 (58) Ϫ/Ϫ were highly selective, because no changes were observed in the levels of other partners of Ranbp2, such as SUMO-1-RanGAP, Nr2e3, and COUP-TFI (data not shown) (89).…”
Section: R2944a-hamentioning
confidence: 99%
“…Ranbp2 modulates the nucleocytoplasmic shuttling of a set of partners that are functionally diverse, due to the direct association of distinct domains of Ranbp2 with nuclear import and export receptors, such as importin-␤ and exportin-1/Crm1, respectively, and other shuttling substrates (22,48,64,79). Hence, we examined changes in the subcellular distribution of some Ranbp2 partners in the RPE between RPE-cre::Ranbp2 ϩ/ϩ and RPE-cre::Ranbp2 Ϫ/Ϫ mice (Fig.…”
Section: Cd11bmentioning
confidence: 99%
“…71 Insufficiency in Nup358 furthermore causes upregulation of the orphan transmembrane tyrosine kinase receptor ErbB2 and suppression of ubiquitylation in response to light stress, which may also contribute to apoptosis suppression in central retina regions of Nup358 +/− mice. 70 Together these studies have revealed a determinant role for Nup358 in glucose, energy and lipid homeostasis in neurons of the CNS and the retina, and implicate Nup358 (and its binding partners) as key player in neuropathic and neurodegenerative diseases. 96 Hypomorphic mutant alleles of Nup154 affect female and male fertility in Drosophila (see above).…”
Section: Tissue-specific Nucleoporin Functionsmentioning
confidence: 94%
“…2 and Table 1), that range from more general functions in nucleocytoplasmic transport, [56][57][58][59] mitosis, [60][61][62] and cellular signaling due to its E3 SUMO ligase activity [63][64][65][66] to tissue-specific functions particularly in neurons and muscle cells. [67][68][69][70][71][72] Moreover, Nup358 interacts with interphase microtubules (MTs) through its N-terminal, leucine-rich domain and overexpression of this MT-targeting domain in CHO cells increased MT bundling and stability, whereas depletion of Nup358 led to a decrease in polarized cell migration and stable MTs. 73 Endogenous Nup358 and a GFP-fusion of Nup358's N-terminal domain were found in the cytoplasm and to colocalize with MTs at cell extensions.…”
Section: Nucleoporins and Cell Migrationmentioning
confidence: 99%
See 1 more Smart Citation